2022
DOI: 10.1002/jgc4.1627
|View full text |Cite
|
Sign up to set email alerts
|

An evidence‐based practice guideline of the National Society of Genetic Counselors for telehealth genetic counseling

Abstract: There are currently no practice guidelines available for genetic counseling using telehealth modalities. This evidence-based practice guideline was developed in response to increasing use of alternative service delivery models for genetic counseling, specifically telephone and video-based genetic counseling (telehealth genetic counseling or THGC). A recent systematic evidence review (SER) compared outcomes of THGC with in-person genetic counseling and found that for the majority of studied outcomes, THGC was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…The increasing complexity of prenatal screening and the associated genetic counseling workload has been observed in many settings, particularly where expanded NIPT options are available. Further research into alternative genetic counseling delivery techniques such as telehealth, web‐based educational videos, and computerized decision aids is needed to help meet the growing demand for prenatal genetic counseling services 98–101 …”
Section: Pre‐ and Post‐test Counseling Challengesmentioning
confidence: 99%
“…The increasing complexity of prenatal screening and the associated genetic counseling workload has been observed in many settings, particularly where expanded NIPT options are available. Further research into alternative genetic counseling delivery techniques such as telehealth, web‐based educational videos, and computerized decision aids is needed to help meet the growing demand for prenatal genetic counseling services 98–101 …”
Section: Pre‐ and Post‐test Counseling Challengesmentioning
confidence: 99%
“…Unfortunately, access to genetic counselors is frequently hampered by geographical location, cost/insurance limitations, and familial or office visit time constraints. [8][9][10][11] With the rapid advances in CF genetics, 4 as well as diagnostic challenges related to genotypes with variable phenotypes, genetic counselors who are current with the most recent CF Foundation guidelines are critical to providing families with accurate and thorough genetic information about CF. 6 To address the access and expertise issues, GC via telemedicine is an appealing option, as it can provide access to highly knowledgeable and skilled individuals who are in a separate location from the patient.…”
Section: Introductionmentioning
confidence: 99%
“…Telemedicine is an effective modality for provision of GC services. [8][9][10] Initial randomized trials of telemedicine efforts by Buchanan et al in 2015 8 showed comparable satisfaction with service provision between in-person and telemedicine GC but noted decreased no-show rates for patients randomized into in-person versus telemedicine appointments for cancer GC. Comparison of costs showed significantly lower costs of service via telemedicine, despite the inclusion of IT costs for telemedicine.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations